Proceedings of the First International Conference on Health, Social Sciences and Technology (ICoHSST 2020) 2021
DOI: 10.2991/assehr.k.210415.026
|View full text |Cite
|
Sign up to set email alerts
|

Family Support For Members in Taking Care of Mental Disordered Patients

Abstract: Problems with the care process of people with mental disorders by family caregivers never lead to concrete solutions. Family support is one of the determinants of the successful recovery of a patient's condition because it reflects the family's efforts in accompanying patients undergoing their daily lives. This study aims to determine various factors that correlate with the support of family caregiver for family members suffering from mental disorders. Families who accompanied the patients while undergoing out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Instrumental support is support in which the family is expected to facilitate all the needs of family members, be it biological, psychological, social, or spiritual. Biological needs are basic needs, as well as material needs that must be met (26). Emotional support, information, and appreciation remain components that cannot be separated because these three components of support strengthen how the family supports older adults in carrying out their role in preventing themselves from the potential for DHF transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Instrumental support is support in which the family is expected to facilitate all the needs of family members, be it biological, psychological, social, or spiritual. Biological needs are basic needs, as well as material needs that must be met (26). Emotional support, information, and appreciation remain components that cannot be separated because these three components of support strengthen how the family supports older adults in carrying out their role in preventing themselves from the potential for DHF transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have observed problems with the regular administration of psychotropic medications. It is one of the most signifcant barriers to integrate mental health services into community health [13,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Zaspokojenie tej potrzeby -jak zauważają Kusumawaty, Surahmat, Martini i Muliyadi (2021) -jest czynnikiem, który w istotny sposób może zmienić trajektorię choroby i zdecydować o ewentualnym sukcesie w powrocie do pełni sił. Jak podkreślają, istnieje silna korelacja pomiędzy siłami pacjenta do przeżycia i wytrwania w procesie leczenia a siłą wsparcia otrzymywaną przez chorego od rodziny (Kusumawaty i in., 2021). W związku z tym zrozumienie, w jaki sposób rodzina oddziałuje na proces zdrowienia, wydaje się niezwykle istotną kwestią.…”
Section: Wsparcie Społeczne I Systemy Wsparcia Dla Osób Doświadczając...unclassified
“…np. Kusumawaty i in., 2021;Pernice-Duca, 2010) -nadal mamy ograniczoną wiedzę, jakie znaczenie mają interakcje i relacje w rodzinie dla pacjenta i jego zdrowia. Z badań Kate, Grovera, Kulhary i Nehry (2013) wynika, że najczęstsze rodzaje wsparcia udzielanego chorym są następujące: wsparcie emocjonalne, informacyjne, instrumentalne oraz poprzez uznanie.…”
Section: Wsparcie Społeczne I Systemy Wsparcia Dla Osób Doświadczając...unclassified